Estudo sobre os mecanismos antinociceptivos periféricos induzidos pela dopamina - Bárbara Formiga Gonçalves de Queiroz (2020)
INTRODUCTION: Dopamine (DA) is an abundant neurotransmitter in the Central Nervous System, exercising cognitive and motor functions, in addition to being identified as an important agent in the descending inhibitory pathway of pain, promoting analgesic effects, whose peripheral mechanisms are not yet well understood. OBJECTIVE: The present study aimed to evaluate the DA antinociceptive action, at the peripheral level, and to investigate the participation of the opioid, cannabinoid, nitrergic systems and potassium channels in this process. METHODS: For this, the paw removal test subjected to compression in mice (Swiss, male, 30-40 g / CEUA Protocol: 196/2018) was used, which showed increased pain sensitivity by PGE2 administration. The study was conducted using pharmacological tools. All drugs were administered intraplantarly, subcutaneously, in a volume of 20 µl (n=5). RESULTS: The administration of DA (5, 20, 80 ng/paw) promoted an antinociceptive effect, in a dose-dependent manner, in animals pretreated with PGE2 (2 µg/paw). This effect was reversed by D2 family antagonists [D2 - Remoxipride (4 µg/paw), D3 - U 99194 (16 µg/paw) and D4 - L-745,870 (16 µg/paw)], but not by antagonists of receivers of the D1 family [D1 - SKF 83566 (2 µg/paw) and D5 - SCH 23390 (1.6 µg/paw)]. However, when administering these same D1 receptor antagonists with a dose of DA (10 µg / paw) that causes hyperalgesia in animals, it was observed that these antagonists were able to reverse the hyperalgesic effect. To evaluate the participation of the opioidergic system, opioid receptor antagonists Naloxone (12.5, 25 and 50 μg/paw), CTOP (20 μg/paw), Naltrindole (15, 30 and 60 μg/paw) and Nor BNI (50, 100 and 200 μg/paw). All of them promoted the reversion of DA-mediated antinociception, except CTOP (µ-opioid receptor antagonist). To investigate the participation of endogenous opioid peptides in the analyzed process, the inhibitor of their degradation, Bestatin (400 μg/paw), was used, which was able to potentiate the antinociceptive effect promoted by a lower dose of DA (5 ng/paw). Similarly, when evaluating the participation of the endocannabinoid system, the use of the endocannabinoid degradation inhibitor 2-AG, JZL184 (4 μg/paw), promoted potentiation of DA-mediated antinociception (5 ng/paw). The same did not happen with the administration of the anandamide degradation inhibitor, MAFP (0.5 μg/paw), and with the transporter inhibitor, VDM11 (2.5 μg/paw), suggesting the participation of the endocannabinoid 2-AG, but not anandamide. To assess the participation of XVII cannabinoid receptors, the animals were treated with CB1 (AM251 - 20, 40 and 80 μg/paw) and CB2 (AM630 - 100 μg/paw) antagonists, and the data obtained suggest, with mediated antinociception reversal by DA, the participation of the two recipients in this event. The involvement of nitric oxide (NO) was confirmed by the reversion of antinociception mediated by DA when the L-NOarg (12, 18 and 24 μg/paw) and L NPA (12, 18 and 24 μg/paw) inhibitors were used. The inhibitors L-NIO (24 μg/paw) and L-NIL (24 μg/paw) did not promote changes in the nociceptive threshold. Accordingly, DA-mediated antinociception appears to depend on the action of soluble guanylate cyclase (sGC) and levels of cyclic guanosine monophosphate (cGMP), data obtained by administering the enzyme inhibitor sGC, ODQ (25, 50 and 100 μg/paw), and the enzyme inhibitor that degrades cGMP, Zaprinast (50 μg/paw). Additionally, the antinociception triggered by DA appears to be related to the opening of voltage-gated potassium channels and low-conductance calcium-activated potassium channels, but not by ATP-sensitive potassium channels and high conductivity calcium-activated potassium channels, data obtained through the use of selective inhibitors for these channels: Tetraethylammonium - 30 μg/paw, Dequalinium - 50 μg/paw, Glibenclamide - 80 μg/paw and Paxilina - 20 μg/paw, respectively. CONCLUSION: Our data suggest that DA-mediated peripheral antinociception is the result of the concomitant activation of D2 family dopaminergic receptors, δ and κ-opioid receptors, CB1 and CB2 cannabinoid receptors and the neuronal isoform of the nitric oxide synthase enzyme, with possible release opioid peptides and 2-AG endocannabinoid. Furthermore, our results indicated the involvement of the sGC enzyme, the second messenger cGMP and the participation of voltage-gated potassium channels and low conductance activated calcium channels in this process.